Certification Allowances as a Means of Improving Teacher Performance - Indriati, Yeni; Perrodin, David D (PPSDP International Journal of Education, 2022)
The purpose of this study is to determine 1) the characteristics of professional teachers who hold educator certificates, 2) what efforts teachers have made to implement the learning process in the classroom, and 3) what efforts teachers have made to improve their performance in order to meet national education goals. This study is a descriptive qualitative study. This research included 18 instructors who already held educator credentials and got professional allowances. Techniques for collecting data include surveys, observation, and documentation. Techniques for data analysis include data reduction, data display, and decision making. According to the study's findings, qualified instructors have strong professional competence but must constantly grow their expertise in a sustainable manner. Furthermore, instructors must seek to better themselves and employ digital skills to enhance the learning process in the classroom in order to raise students' enthusiasm in engaging in learning. This study focuses on the hurdles or issues encountered by qualified instructors, particularly throughout the classroom learning process. With this research, it is intended that it would help trained instructors overcome obstacles that arise during the learning process in the classroom, allowing them to reach the required level of national education.